Non-suicidal self-injury function: prevalence in adolescents with depression and its associations with non-suicidal self-injury severity, duration and suicide - Shen, Ying; Hu, Yingzi; Zhou, Yongjie; Fan, Xiwang (Frontiers in Psychiatry, 2023)
Background: Given that adolescents with depression are at the highest risk for non-suicidal self-injury (NSSI), a thorough understanding of their NSSI functions, as well as associations between functions and severe behavioral consequences, is essential for risk assessment and invention development. Methods: Adolescents with depression from 16 hospitals across China, for whom data was available regarding their NSSI function, frequency, number of methods used, time characteristics, and suicide history were included. Descriptive statistical analyses were performed to determine the prevalence of NSSI functions. Regression analyses were conducted to explore the relationship between NSSI functions and behavioral characteristics of NSSI and suicide attempts. Results: Affect regulation was the primary function of NSSI and followed by anti-dissociation in adolescents with depression. Females recognized automatic reinforcement functions more frequently than males, while males had a higher prevalence of social positive reinforcement functions. Automatic reinforce functions played the prominent role in associations between NSSI functions and all the severe behavioral consequences. Specifically, functions of anti-dissociation, affect regulation, and self-punishment were all associated with NSSI frequency, while higher levels of endorsements for anti-dissociation and self-punishment were linked to more NSSI methods, and greater level of endorsement for anti-dissociation was related to longer NSSI duration. Only the increase in endorsement of self-punishment was associated with a greater hazard of suicide attempts. Conclusion: The dominant functions of NSSI in adolescents with depression was automatic reinforcement, specifically affect regulation. And prevalence of NSSI function differed between males and females. Anti-dissociation and self-punishment seemed to be the most risky factors as they were linked to severe NSSI or suicide behaviors. More attention should be given to these functions in risk evaluation, and the targeted interventions should be developed accordingly in a timely manner.